A Gap Analysis Assessing the Perceptions of Primary Care Physicians in the Management of Kidney Recipients After Transplantation. (December 2019) - Famure, Olusegun; Caballero, Myra N.; Li, Anna; Tang, Rosalind; Chen, Pei Xuan; Ashwin, Monika; Adcock, Leslie; Schiff, Jeffrey; Kim, S. Joseph
Objectives: To examine the practice patterns and perceptions of primary care physicians in the management of chronic diseases in kidney recipients, assess care provided to recipients, and identify barriers to the optimal delivery of primary care to recipients. Methods: A self-administered questionnaire on the primary care of kidney recipients was developed and implemented. The survey investigated physician comfort and practice patterns in providing preventive and chronic care to recipients, patient self-management support, and physician perceptions on communication with transplant centers and barriers to ideal care. Results: A total of 210 physicians completed the survey (response rate of 22%). Among the respondents, 73% indicated they were currently providing care to kidney recipients. The majority of physicians specified that they rarely (57%) or never (20%) communicate with transplant centers. Most physicians felt comfortable providing care to recipients for non-transplant-related issues (92.5%), vaccinations (85%), and periodic health examinations (94%). The majority (75.3%) of physicians felt uncomfortable managing the immunosuppressive medications of recipients. Physicians' most commonly stated barriers to delivering optimal care to recipients were insufficient guidelines provided by the transplant center (68.9%) and lack of knowledge in managing recipients (58.8%). Suggested resources by physicians to improve their comfort level in managing recipients included guidelines and continuing medical educational activities related to transplantation. Conclusions: Our results suggest that there are barriers to delivering optimal primary care to kidney recipients. The approach to providing resources needed to bridge the knowledge gap for physicians in the management of recipients requires further exploration.